PEMIKIRAN FAZLUR RAHMAN TENTANG METODOLOGI SUNNAH DAN HADIS [Kajian Buku Islamic Methodology in History] - Sanaky, Hujair AH. (Al-Mawarid Jurnal Hukum Islam, 2006)
Fazlur Rahman is one of an International Moselm scholar has paid attention to the Islamic thought reforming in moslem world. Rahman had concerned on the methodology of Islamic thought reform, and this concern can be understood from one of his works ( book) Islamic Methodology in History (Indonesian translation Membuka Pintu Ijtihad). This book tries to describe the development of four sources of Islamic thought Alquran, Sunnah, Ijtihad and Ijmaâ evolutively and historically. According to Rahman as the founding of neomodernism in Islam that Moslem now need to deconstruct and reconstruct the historical heritages of Islam in all aspects. Kata kunci: metodologi, sejarah, pemikiran, dan pembaharuan